Factors contributing to back pain the among palm oil workers in Bau-Lundu districts Sarawak - Nanthakumar, A/L Thirunavukkarasu (Universiti Malaysia Sarawak (UNIMAS), 2012)
This cross sectional study was conducted to identify the prevalence of back pain and the factors contributing to back pain among the palm oil plantation workers in the district of Bau- Lundu from January 2012 to April 2012. Data was collected by face-to-face interview using a structured questionnaire as a guide. A total of 230 respondents were interviewed with a 46% response rate. The mean age of the workers was 28.7 ± 5.00 years. The majority of the workers were male 83.9% and most of them were Indonesian at 96.5%. These workers were hired on a contract basis at (96.5%). Most of them had received primary level of education at 98.2%. The mean monthly salary is RMI121 + 286.7. The median duration of work in the palm oil plantation was about 3.9 years. The prevalence of smoking is about 72.6% among the workers and Bartak estate have the highest prevalence of back pain among their workers which is 90.2%. The proportion of back pain that was related to work or back pain experienced throughout their working experiences in the last 12 months in the plantation were 82.2%. The proportion of back pain is higher among harvesters which contribute to about 86% compared to general workers which is about 70.7%. The results of this study showed a high prevalence of work related back pain could have been contributed by their daily activities that require active movement and involve manual material handling. Those workel~s who handle heavy material incorrectly are at higher risk of getting back pain by 54 fold which signify the importance of handling the heavy material correctly. The findings of this study wit! help in developing a health promotion module at work place.